Solid-state composite electrolyte, preparation method thereof and battery
By using solid-state composite electrolytes in lithium-ion batteries, the lithium supplement agent is wrapped in the polymer electrolyte layer, the problems of irreversible capacity loss of lithium-ion batteries and the failure of lithium supplement agents are solved, and efficient lithium ion release and battery stability are achieved.
Patent Information
- Application Number
- CN202411758549.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Existing lithium-ion batteries are prone to irreversible capacity loss during use. The poor packaging of traditional diaphragm materials on lithium supplements leads to failure of lithium supplements, and the positive electrode lithium supplements are exposed to the external environment to reduce the efficiency of lithium release.
Solid-state composite electrolyte is used to prevent lithium release by wrapping the lithium supplement agent in the polymer electrolyte layer to avoid contact with the outside world, thereby preventing lithium release. After the electrolyte is infused, a SEI film is formed on the negative electrode surface to orderly release lithium ions.
Effectively prevent lithium replenishment agents from releasing lithium, improve lithium replenishment efficiency, enhance ionic conductivity, reduce the amount of electrolyte, and improve the stability of the battery and the safety of thermal runaway.
Smart Images

Figure CN119725706A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a solid composite electrolyte and a preparation method thereof and a battery. Background Art
[0002] The capacity decay problem of lithium-ion batteries is a problem that has not been completely solved in the current development of lithium-ion batteries. Lithium-ion batteries are very prone to irreversible capacity loss under electrical abuse, thermal abuse, and mechanical abuse. The low initial efficiency of the anode is a major source of capacity loss for the entire battery. The solution to the problem of lithium battery capacity loss is to optimize the electrochemical system of the battery to suppress capacity decay during use, but these are all auxiliary improvements to capacity decay, and do not fundamentally improve and prevent capacity loss. In response to the problem of lithium battery capacity loss, lithium is also replenished on the surface of the positive and negative electrode materials to make up for the irreversible lithium loss caused by the first lithium insertion process of the negative electrode. However, whether it is a positive electrode lithium replenisher or pre-lithiation of the negative electrode, it will cause a linear increase in cost and difficulty of manufacturing, and the use of a lithium replenisher at the positive electrode will also reduce the volume energy density of the battery cell.
[0003] Studies have shown that the use of a lithium replenisher inside the diaphragm can effectively improve the lithium loss caused by the formation of the SEI film during the first lithium insertion of the negative electrode and the consumption of active lithium in subsequent side reactions. Therefore, it is generally believed that the improvement and prevention of irreversible losses in lithium-ion batteries through diaphragms is a very promising approach. Lithium replenishment of the diaphragm can be coated and multi-layered, which can improve the irreversible lithium loss. However, the surfaces of most diaphragms and the currently commercially available PE, PP, and PE / PP / PE diaphragms are not feasible, and the diaphragm structure needs to be reorganized and defined. If the diaphragm is linked to a polymer solid electrolyte, the lithium replenisher is used as a Lewis acid to promote the polymerization reaction of the polymer monomers. After the electrolyte is perfused, the polymer expands to release the lithium replenisher. After the lithium is released, the material itself is a good inert filler, which can improve the local crystallization state of the polymer, promote the dissolution of lithium salts, and enhance Li + The polymerization of chain segment polar groups helps to generate free volume and enhance ionic conductivity, while compensating for the initial lithium insertion process of the negative electrode and increasing the initial effect of the anode.
[0004] In order to address the irreversible lithium loss, positive electrode lithium replenishers are added during the positive electrode slurry process, which will cause lithium release due to the contact of the lithium replenisher with the external environment, reducing the lithium replenishment effect. In addition, the lithium replenisher currently forms inactive residues after the positive electrode releases lithium, affecting the cycle performance of the battery cell and increasing the internal resistance. The use of lithium foil or lithium powder to replenish lithium on the negative electrode side is expensive and uncontrollable. The above problems also exist when using pre-lithiated negative electrodes. Summary of the invention
[0005] In view of this, the present invention is committed to providing a solid composite electrolyte and a preparation method and a battery thereof, so as to solve the problems in the prior art that the addition of a positive electrode lithium supplement during the positive electrode homogenization process will cause lithium release due to the contact of the lithium supplement with the external environment, thereby reducing the lithium supplement effect; the lithium supplement using lithium foil or lithium powder on the negative electrode side is expensive and uncontrollable, and the use of a pre-lithiated negative electrode increases the difficulty of manufacturing and reduces the yield of the finished product; the traditional diaphragm material wraps the lithium supplement, which will result in the lithium supplement being unable to be released, causing the lithium supplement to fail.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] A first aspect of the present invention provides a solid composite electrolyte, the solid composite electrolyte comprising a lithium supplement and a polymer electrolyte wrapped on the surface of the lithium supplement;
[0008] The polymer electrolyte includes a solid solvent polymer and a lithium salt, and the lithium salt is dissolved in the solid solvent polymer.
[0009] Optionally, the lithium replenisher, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte satisfy the relationship: 0.6≤m1 / (m1+m2+m3)≤0.9, wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt; preferably, the lithium replenisher, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte satisfy the relationship: 0.75≤m1 / (m1+m2+m3)≤0.85.
[0010] Optionally, the mass ratio of the lithium salt to the lithium supplement agent is 1:0.1-5, preferably 1:0.5-1.5.
[0011] Optionally, the lithium supplement includes a lithium-containing oxide; optionally, the lithium-containing oxide is selected from at least one of Li5FeO4, LiNiO2, Li2NiO2, Li2O, Li2O2, Li2MnO3, Li6MnO4, Li6CoO4 and Li5ReO6; and / or, the lithium salt is selected from at least one of LiTFSI, LiPF6, LiBF4, LiBOB, LiFSI and LiODFB; and / or, the solid solvent polymer is selected from at least one of poly(1,3-dioxolane), polyethylene oxide, polyvinyl alcohol, polymethyl methacrylate and polyvinylidene fluoride.
[0012] Optionally, the solid composite electrolyte further comprises glass fibers, and the glass fibers are dispersed in the solid solvent polymer; optionally, based on the total mass of the solid composite electrolyte, the content of the glass fibers is 0.05 to 10 wt%, preferably 1 to 5 wt%.
[0013] A second aspect of the present invention provides a method for preparing a solid composite electrolyte, the preparation method comprising the following steps:
[0014] S1, performing a first mixing treatment on a solid solvent polymer monomer and a lithium supplement agent to obtain a first slurry;
[0015] S2, performing a second mixing process on the first slurry and the lithium salt to obtain a second slurry;
[0016] S3, heating and drying the second slurry.
[0017] Optionally, the viscosity of the first slurry is 500-10000Cp, preferably 1000-3000Cp; and / or the solid content of the first slurry is 10-50%, preferably 15-30%; and / or the viscosity of the second slurry is 50-20000Cp, preferably 50-200Cp; and / or the solid content of the second slurry is 1-20%, preferably 5-10%; and / or the solid solvent polymer monomer is selected from at least one of 1,3-epoxypentane, ethylene oxide, vinyl acetate, methyl methacrylate and 1,1-difluoroethylene.
[0018] Optionally, in step S1, the conditions of the first mixing treatment include: temperature of 40-60°C, time of 10-120 min, and stirring speed of 800-1500 rpm; and / or, in step S2, the conditions of the second mixing treatment include: temperature of 40-60°C, time of 30-60 min, and stirring speed of 600-900 rpm; and / or, in step S3, the conditions of the heating treatment include: temperature of 40-60°C, time of 30-90 min; and / or, the conditions of the drying treatment include: temperature of 40-60°C, time of 60-150 min.
[0019] Optionally, the preparation method further comprises: adding glass fibers in the second mixing process to obtain a second slurry containing glass fibers.
[0020] The third aspect of the present invention provides a battery, which includes an electrode assembly and an electrolyte, wherein the electrode assembly includes a positive electrode, a negative electrode and a solid electrolyte layer, and the solid electrolyte layer is the above-mentioned solid composite electrolyte or a solid composite electrolyte prepared according to the above-mentioned preparation method.
[0021] Through the above technical solution, the beneficial technical effects of the present invention are:
[0022] (1) The solid composite electrolyte of the present invention wraps the lithium supplement agent between the polymer electrolyte layers, which does not come into contact with the outside world such as air. The lithium supplement agent will not release lithium when in contact with the air, which can effectively prevent the lithium supplement agent from releasing lithium and improve the lithium supplement efficiency. The present invention places the lithium supplement agent between the polymer solid electrolyte layers and then performs electrolyte perfusion. During the first charging process, a SEI film is first formed on the surface of the negative electrode, wherein the redox potential of the lithium supplement agent is lower than that of the positive electrode material, so that lithium ions are released first during the charging process, thereby achieving orderly lithium release.
[0023] (2) In the solid composite electrolyte of the present invention, after the lithium supplement agent releases lithium, the inactive substance remains in the polymer system as an inert filler, which can increase the amorphous proportion of the polymer and enhance the Li + The polymerization of polar groups in the chain segments helps to generate free volume and enhance ionic conductivity.
[0024] (3) The solid composite electrolyte of the present invention can reduce the amount of electrolyte used, the solid electrolyte layer is not prone to high temperature deformation, and the stability is significantly improved compared to the diaphragm. The polymer solid electrolyte layer has a high Young's modulus, and lithium dendrites cannot penetrate it, which can effectively reduce the probability of thermal runaway and the peak temperature during thermal runaway. The solvent in the electrolyte infiltrates the solid composite electrolyte, which can enhance the flexibility of the solid electrolyte layer, improve the "solid-solid contact" problem between the solid electrolyte layer and the positive and negative electrodes, and accelerate the electrochemical reaction rate.
[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0027] Figure 1 Shown is a SEM image of the solid composite electrolyte prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention discloses a solid composite electrolyte and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0029] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] In order to solve the problems in the prior art that the addition of positive electrode lithium supplement agent during the positive electrode homogenization process will cause lithium release due to the contact of the lithium supplement agent with the external environment, thereby reducing the lithium supplement effect; the lithium supplement of lithium foil or lithium powder on the negative electrode side is expensive and uncontrollable, the use of pre-lithiated negative electrode increases the difficulty of manufacturing and reduces the yield of finished products; the traditional diaphragm material wraps the lithium supplement agent, which will cause the lithium supplement agent to be unable to be released, resulting in the failure of the lithium supplement agent, the present invention adopts the following technical solutions:
[0035] A first aspect of the present invention provides a solid composite electrolyte, the solid composite electrolyte comprising a lithium supplement and a polymer electrolyte wrapped on the surface of the lithium supplement;
[0036] The polymer electrolyte includes a solid solvent polymer and a lithium salt, and the lithium salt is dissolved in the solid solvent polymer.
[0037] The solid composite electrolyte of the present invention wraps the lithium supplement agent between the polymer electrolyte layers, which does not come into contact with the outside world such as air. The lithium supplement agent will not release lithium when in contact with the air, which can effectively prevent the lithium supplement agent from releasing lithium and improve the lithium supplement efficiency. The present invention places the lithium supplement agent between the polymer solid electrolyte layers and then performs electrolyte perfusion, so that an SEI film is first formed on the negative electrode surface during the first charging process, wherein the redox potential of the lithium supplement agent is lower than that of the positive electrode material, so that lithium ions are released first during the charging process, thereby enabling orderly lithium release.
[0038] The solid composite electrolyte of the present invention can also reduce the amount of electrolyte used. The solid electrolyte layer containing the solid composite electrolyte of the present invention is not prone to high temperature deformation, and its stability is significantly improved compared to the diaphragm. The polymer solid electrolyte layer of the present invention has a high Young's modulus, and lithium dendrites cannot pierce it, which can effectively reduce the probability of thermal runaway and the peak temperature during thermal runaway. In the present invention, the solvent in the electrolyte can enhance the flexibility of the solid electrolyte layer while infiltrating the solid composite electrolyte, improve the "solid-solid contact" problem between the solid electrolyte layer and the positive and negative electrodes, and accelerate the electrochemical reaction rate.
[0039] According to the present invention, a suitable solid solvent polymer is required in the solid composite electrolyte to ensure that the migration and ion conductivity of lithium ions are not affected while dissolving the lithium salt. Exemplarily, the lithium supplement agent, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte can satisfy the relationship: 0.6≤m1 / (m1+m2+m3)≤0.9, wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium supplement agent, and m3 represents the mass of the lithium salt. In the present invention, if there are too many solid solvent polymers, the number of lithium ion migration and the ion conductivity may decrease; if there are too few solid solvent polymers, the lithium salt may not be completely dissolved. Preferably, the lithium supplement agent, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte satisfy the relationship: 0.75≤m1 / (m1+m2+m3)≤0.85.
[0040] According to the present invention, the ratio of a suitable lithium salt to a lithium supplement has excellent ionic conductivity and ion mobility. The mass ratio of the lithium salt to the lithium supplement may be 1:0.1 to 5. Exemplarily, the mass ratio of the lithium salt to the lithium supplement may be any value among 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4 and 1:5 or any value within the range of values composed of any two of the above values. In the present invention, if the proportion of the lithium salt is too much, the lithium salt may not be dissolved, thereby reducing the overall ionic conductivity; if the proportion of the lithium salt is too little, the ionic conductivity may be low, thereby failing to meet the high-rate use conditions. Preferably, the mass ratio of the lithium salt to the lithium supplement may be 1:0.5 to 1.5.
[0041] According to the present invention, the lithium supplement agent may include a lithium-containing oxide; illustratively, the lithium-containing oxide may be selected from at least one of Li5FeO4, LiNiO2, Li2NiO2, Li2O, Li2O2, Li2MnO3, Li6MnO4, Li6CoO4 and Li5ReO6. In the solid composite electrolyte of the present invention, after the lithium supplement agent has completed lithium release, the inactive substance (such as iron oxide) can remain in the polymer system as an inert filler, which can increase the amorphous ratio of the polymer and enhance the Li + The polymerization of polar groups in the chain segments helps to generate free volume and enhance ionic conductivity.
[0042] Exemplarily, the lithium salt may be selected from at least one of LiTFSI, LiPF6, LiBF4, LiBOB, LiFSI and LiODFB.
[0043] Exemplarily, the solid solvent polymer may be selected from at least one of poly(1,3-dioxolane) (PDOL), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF).
[0044] In a preferred embodiment of the present invention, the lithium-containing oxide is Li5FeO4, the lithium salt is LiTFSI, and the solid solvent polymer is poly(1,3-dioxolane). In this embodiment, the solid composite electrolyte can have excellent ionic conductivity and can increase the lithium ion migration number.
[0045] According to the present invention, the solid composite electrolyte may further include glass fibers, and the glass fibers are dispersed in the solid solvent polymer. In the present invention, the rigidity of the solid composite electrolyte can be maintained by adding glass fibers.
[0046] According to the present invention, the appropriate amount of glass fiber added can maintain the rigidity of the solid composite electrolyte while reducing the polymer glass transition temperature and increasing the solubility of the lithium salt. Based on the total mass of the solid composite electrolyte, the content of the glass fiber can be 0.05-10wt%. Exemplarily, the content of the glass fiber can be any value among 0.05-10wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt% and 10wt%, or any value within the range of any two of the above values. In the present invention, if the amount of glass fiber added is too low, the rigidity of the solid composite electrolyte may not be guaranteed; if the amount of glass fiber added is too high, the polymer electrolyte may lose its toughness. Preferably, the content of the glass fiber can be 1-5wt%.
[0047] A second aspect of the present invention provides a method for preparing a solid composite electrolyte, the preparation method comprising the following steps:
[0048] S1, performing a first mixing treatment on a solid solvent polymer monomer and a lithium supplement agent to obtain a first slurry;
[0049] S2, performing a second mixing process on the first slurry and the lithium salt to obtain a second slurry;
[0050] S3, heating and drying the second slurry.
[0051] According to the present invention, the viscosity of the suitable first slurry can increase the production efficiency of the solid composite electrolyte. In the present invention, the viscosity of the first slurry can be 500-10000Cp. Exemplarily, the viscosity of the first slurry can be any value among 500Cp, 1000Cp, 3000Cp, 5000Cp, 7000Cp, 9000Cp and 10000Cp or any value within the range of any two of the above values. In the present invention, if the viscosity of the first slurry is too high, a thin layer may not be achieved; if the viscosity of the first slurry is too low, the generation of the electrolyte layer may be affected. Preferably, the viscosity of the first slurry can be 1000-3000Cp.
[0052] According to the present invention, the solid content of the suitable first slurry can control the thickness of the film while ensuring film formation. In the present invention, the solid content of the first slurry can be 10-50%. Exemplarily, the solid content of the first slurry can be any value among 10%, 20%, 30%, 40% and 50% or any value within the range of values composed of any two of the above values. In the present invention, if the solid content of the first slurry is too high, it may be difficult to form a film; if the solid content of the first slurry is too low, it may be difficult to control the thickness of the film. Preferably, the solid content of the first slurry can be 15-30%.
[0053] According to the present invention, the viscosity of the suitable second slurry can improve the production efficiency of the solid composite electrolyte. In the present invention, the viscosity of the second slurry can be 50 to 20000Cp. Exemplarily, the viscosity of the second slurry can be any value among 50Cp, 100Cp, 1000Cp, 10000Cp, 15000Cp and 20000Cp or any value within the range of any two of the above values. In the present invention, if the viscosity of the second slurry is too high, it may affect the subsequent coating; if the viscosity of the second slurry is too low, the solvent may be wasted and the cost may be increased. Preferably, the viscosity of the second slurry can be 50 to 200Cp.
[0054] According to the present invention, the solid content of the suitable second slurry can control the thickness of the film while ensuring film formation. In the present invention, the solid content of the second slurry can be 1-20%. For example, the solid content of the second slurry can be any value among 1%, 5%, 10%, 15% and 20%, or any value within the range of any two of the above values. In the present invention, if the solid content of the second slurry is too high, it may be difficult to form a film; if the solid content of the second slurry is too low, it may be difficult to control the thickness of the film. Preferably, the solid content of the second slurry can be 5-10%.
[0055] According to the present invention, the solid solvent polymer monomer may be selected from at least one of 1,3-epoxypentane, ethylene oxide, vinyl acetate, methyl methacrylate and 1,1-difluoroethylene.
[0056] According to the present invention, in step S1, the conditions of the first mixing treatment may include: a temperature of 40 to 60° C., a time of 10 to 120 min, and a stirring speed of 800 to 1500 rpm.
[0057] According to the present invention, in step S2, the conditions of the second mixing treatment may include: a temperature of 40 to 60° C., a time of 30 to 60 min, and a stirring speed of 600 to 900 rpm.
[0058] According to the present invention, in step S3, the conditions for the heating treatment may include: a temperature of 40 to 60° C. and a time of 30 to 90 min; and / or, the conditions for the drying treatment may include: a temperature of 40 to 60° C. and a time of 60 to 150 min.
[0059] According to the present invention, the preparation method may further include: adding glass fibers in the second mixing process to obtain a second slurry containing glass fibers.
[0060] The third aspect of the present invention provides a battery, which includes an electrode assembly and an electrolyte, wherein the electrode assembly includes a positive electrode, a negative electrode and a solid electrolyte layer, and the solid electrolyte layer is the above-mentioned solid composite electrolyte or a solid composite electrolyte prepared according to the above-mentioned preparation method.
[0061] The electrolyte used in the present invention is a conventional solvent in the art. For example, the electrolyte can be selected from at least one of ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC), fluoroethylene carbonate (FEC) and propylene carbonate (PC).
[0062] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0063] Example 1
[0064] (1) In a glove box with an argon atmosphere (O2<0.1ppm, H2O<0.1ppm), 1,3-epoxypentylene and LiTFSI were added for a first mixing treatment, wherein the mass ratio of 1,3-epoxypentylene to LiTFSI was 1:0.125, the temperature of the first mixing treatment was 50°C, the time was 45min, the stirring speed was 100rpm, and the first slurry was obtained after the mixed material became clear. Li5FeO4 with a mass of 12.5wt% relative to 1,3-epoxypentylene was added to the first slurry and a second mixing treatment was performed, wherein the temperature of the second mixing treatment was 30°C, the time was 45min, the stirring speed was 120rpm, and after the solution became viscous, a glass fiber film with a diameter of 19mm was placed in a bottle for full penetration, and then the film after penetration was taken out and placed in a sealed glass jar to obtain a second slurry. The second slurry was heated at 45°C for 12 hours for full polymerization. After the reaction is completed, transfer to a 45°C vacuum drying oven and vacuum dry for 2 hours to drain the residual small molecule liquid to obtain Li5FeO4-P-DOL, which is the solid composite electrolyte of this embodiment. The mass relationship of the lithium replenisher (Li5FeO4), lithium salt (LiTFSI) and solid solvent polymer (poly (1,3-dioxolane)) in the solid composite electrolyte of this embodiment is m1 / (m1+m2+m3)=0.8 (wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt); the mass ratio of the lithium salt to the lithium replenisher is 1:1. The SEM image of the solid composite electrolyte of this embodiment is shown in Figure 1 ,pass Figure 1 It can be seen that the solid composite electrolyte is a mixed structure of DOL, LiTFSI, and Li5FeO4. Among them, Li5FeO4 has the property of releasing lithium, which can make up for the irreversible capacity loss caused by the formation of SEI during the first lithium insertion of the negative electrode material and enhance the energy density of the battery cell. The presence of DOL can inhibit the reduction of lithium replenishment efficiency caused by the release of lithium from the lithium replenisher during use. The solid composite electrolyte uses the high shear modulus of the polymer to inhibit the vertical growth of lithium dendrites.
[0065] (2) Lithium foil is used as the negative electrode active material, and it is bonded to copper foil to obtain a negative electrode sheet with a size of 100 mm × 55 mm. Ternary material is used as the positive electrode active material, mixed with a conductive agent, a binder, etc., coated on an aluminum foil, and made into a positive electrode sheet after drying, pressing and other processes. The size of the positive electrode sheet is 96 mm × 51 mm. The solid composite electrolyte of this embodiment is used as a diaphragm. The electrolyte is 1M LiPF6, dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The assembly process adopts a soft pack lamination method for assembly, and the positive electrode sheet, diaphragm, and negative electrode sheet are stacked in order to obtain a battery cell.
[0066] Example 2
[0067] The preparation method of the solid composite electrolyte of this embodiment is the same as that of embodiment 1, except that the mass ratio of 1,3-epoxypentane to LiTFSI is 1:0.1875. The mass relationship of the lithium replenisher (Li5FeO4), lithium salt (LiTFSI) and solid solvent polymer (poly (1,3-dioxolane)) in the solid composite electrolyte of this embodiment is m1 / (m1+m2+m3)=0.76 (wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt); the mass ratio of the lithium salt to the lithium replenisher is 1:1.46.
[0068] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0069] Example 3
[0070] The preparation method of the solid composite electrolyte of this embodiment is the same as that of embodiment 1, except that the mass ratio of 1,3-epoxypentane to LiTFSI is 1:0.0625. The mass relationship of the lithium replenisher (Li5FeO4), lithium salt (LiTFSI) and solid solvent polymer (poly (1,3-dioxolane)) in the solid composite electrolyte of this embodiment is m1 / (m1+m2+m3)=0.84 (wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt); the mass ratio of the lithium salt to the lithium replenisher is 1:2.
[0071] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0072] Example 4
[0073] The preparation method of the solid composite electrolyte of this embodiment is the same as that of embodiment 1, except that the mass of the added Li5FeO4 is 20.8wt% relative to the mass of 1,3-epoxypentane. The mass relationship of the lithium replenisher (Li5FeO4), lithium salt (LiTFSI) and solid solvent polymer (poly(1,3-dioxolane)) in the solid composite electrolyte of this embodiment is m1 / (m1+m2+m3)=0.75 (wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt); the mass ratio of the lithium salt to the lithium replenisher is 1:1.67.
[0074] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0075] Example 5
[0076] The preparation method of the solid composite electrolyte of this embodiment is the same as that of embodiment 1, except that the mass of the added Li5FeO4 is 4.2wt% relative to the mass of 1,3-epoxypentane. The mass relationship of the lithium replenisher (Li5FeO4), lithium salt (LiTFSI) and solid solvent polymer (poly(1,3-dioxolane)) in the solid composite electrolyte of this embodiment is m1 / (m1+m2+m3)=0.86 (wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt); the mass ratio of the lithium salt to the lithium replenisher is 1:2.98.
[0077] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0078] Example 6
[0079] The preparation method of the solid composite electrolyte in this embodiment is generally the same as that in Embodiment 1, except that no glass fiber film is added.
[0080] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0081] Comparative Example 1
[0082] The preparation method of the solid composite electrolyte in this comparative example is generally the same as that in Example 1, except that Li5FeO4 is not added.
[0083] The specific preparation method includes: in a glove box with an argon atmosphere (O2<0.1ppm, H2O<0.1ppm), 1,3-epoxypentane and LiTFSI are added for a first mixing treatment, wherein the mass ratio of 1,3-epoxypentane and LiTFSI is 1:0.125, the temperature of the first mixing treatment is 50°C, the time is 45min, the stirring speed is 100rpm, and the first slurry is obtained after the mixed material becomes clear. A glass fiber film with a diameter of 19mm is placed in a bottle for full penetration, and then the film is taken out and placed in a sealed glass jar to obtain a second slurry. The second slurry is continued to be heated at 45°C for 12 hours for full polymerization. After the reaction is completed, it is transferred to a 25°C vacuum drying oven and vacuum dried for 2 hours to drain the residual small molecule liquid to obtain P-DOL, which is the solid composite electrolyte of this comparative example.
[0084] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0085] Comparative Example 2
[0086] The preparation method of the solid composite electrolyte in this comparative example is generally the same as that in Example 1, except that LiTFSI is not added.
[0087] The specific preparation method includes: in a glove box with an argon atmosphere (O2<0.1ppm, H2O<0.1ppm), 1,3-epoxypentane and Li5FeO4 are added for a second mixing treatment, the amount of Li5FeO4 added relative to the mass of 1,3-epoxypentane is 12.5wt%, the temperature of the second mixing treatment is 30°C, the time is 12 hours, the stirring speed is 100rpm, and after the solution becomes viscous, a glass fiber film with a diameter of 19mm is placed in a bottle for full penetration, and then the film is taken out and placed in a sealed glass jar to obtain a second slurry. The second slurry is continued to be heated at 45°C for 12 hours for full polymerization. After the reaction is completed, it is transferred to a 25°C vacuum drying oven and vacuum dried for 2 hours to drain the residual small molecule liquid to obtain Li5FeO4-DOL, which is the solid composite electrolyte of this comparative example.
[0088] The preparation method of the battery cell of this embodiment is generally the same as that of Embodiment 1.
[0089] Comparative Example 3
[0090] Lithium foil is used as the negative electrode active material, which is bonded to copper foil to obtain a negative electrode sheet with a size of 100mm×55mm. Ternary materials are used as positive electrode active materials, which are mixed with conductive agents, binders, etc., coated on aluminum foil, and dried, pressed, and made into positive electrode sheets with a size of 96mm×51mm. PE-based film is used as a diaphragm. The electrolyte is 1M LiPF6, dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The assembly process is assembled by soft-pack lamination, and the positive electrode sheet, diaphragm, and negative electrode sheet are stacked in order to obtain a battery cell.
[0091] Test Example 1
[0092] The battery cells prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were hot pressed and placed in an aluminum-plastic film for top and side sealing. The electrolyte was injected into the battery, the battery after injection was sealed, and the prepared battery was subjected to formation treatment. When comparing the electrochemical properties of different positive electrode sheets, the load of the negative electrode was basically consistent. The charge and discharge cut-off voltage was set to 2.8-4.2V, the charge and discharge current was 1A / g, and the test was terminated after 2000 cycles. The test results of the batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1.
[0093] Among them, the injection coefficient (g / Ah) is the amount of electrolyte added divided by the design capacity of the battery cell.
[0094] The test method for the first efficiency includes: after the battery is manufactured, it is first charged to 3.75V with a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.25V with a constant current of 0.33C, and then charged to I≤0.05C with a constant voltage of 4.25V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.8V with a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.8V with a constant current of 0.1C to obtain the discharge capacity C3, and discharged to 2.8V with a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated according to (C2+C3+C4) / (C0+C1)*100%.
[0095] The test method of 2000 cycle capacity retention rate includes: 1. After the capacity division is completed, the battery is first charged to 4.25V with a constant current of 1C, and then charged to I≤0.05C with a constant voltage of 4.25V; 2. After standing for 5 minutes, the battery is discharged to 2.8V with a constant current of 1C to obtain the discharge capacity C1; 3. Standing for 30 minutes. Repeat steps 1-3 1999 times to obtain the discharge capacity C 2000 ; 2000 cycles capacity retention rate according to (C 2000 ) / (C1)*100% is calculated.
[0096] Contact angle measurements can be made using optical contact angle measuring instruments, ranging from manual instruments to fully automated systems. In the sessile drop method, a drop of liquid (usually water) is placed on a solid sample, an image of the drop is captured by a high-resolution camera, and the angle is then automatically measured by software.
[0097] The 200°C area shrinkage test method includes: taking a 10cm*10cm diaphragm area as S1, placing it at 200°C for 2 hours and measuring the area as S2, and the shrinkage rate is y=1-(S2 / S1).
[0098] Table 1
[0099]
[0100]
[0101] It can be seen from Table 1 that, by comparing Examples 1 to 6 with Comparative Examples 1 to 3, the solid composite electrolyte prepared by the present invention is used for the diaphragm, which can effectively reduce the amount of liquid electrolyte and the area shrinkage at 200°C, and improve the initial coulombic efficiency and capacity retention rate. By comparing the contact angle test results of each embodiment and the comparative example, it can be seen that the introduction of Li5FeO4 can fully reduce the contact angle of the diaphragm, accelerate the wetting, form a polymer solid electrolyte layer under the plasticization effect with the polymer, enhance the contact with the positive and negative electrode surfaces, and improve the solid-solid contact interface.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A solid composite electrolyte, characterized in that: The solid composite electrolyte comprises a lithium supplement agent and a polymer electrolyte wrapped on the surface of the lithium supplement agent; The polymer electrolyte includes a solid solvent polymer and a lithium salt, and the lithium salt is dissolved in the solid solvent polymer.
2. The solid composite electrolyte according to claim 1, characterized in that The lithium replenisher, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte satisfy the relationship: 0.6≤m1 / (m1+m2+m3)≤0.9, wherein m1 represents the mass of the solid solvent polymer, m2 represents the mass of the lithium replenisher, and m3 represents the mass of the lithium salt; Preferably, the lithium supplement agent, the lithium salt and the solid solvent polymer contained in the solid composite electrolyte satisfy the relationship: 0.75≤m1 / (m1+m2+m3)≤0.
85.
3. The solid composite electrolyte according to claim 1, characterized in that: The mass ratio of the lithium salt to the lithium supplement is 1:0.1-5, preferably 1:0.5-1.
5.
4. The solid composite electrolyte according to claim 1, characterized in that: The lithium supplement comprises a lithium-containing oxide; optionally, the lithium-containing oxide is selected from at least one of Li5FeO4, LiNiO2, Li2NiO2, Li2O, Li2O2, Li2MnO3, Li6MnO4, Li6CoO4 and Li5ReO6; And / or, the lithium salt is selected from at least one of LiTFSI, LiPF6, LiBF4, LiBOB, LiFSI and LiODFB; And / or, the solid solvent polymer is at least one selected from poly(1,3-dioxolane), polyethylene oxide, polyvinyl alcohol, polymethyl methacrylate and polyvinylidene fluoride.
5. The solid composite electrolyte according to any one of claims 1 to 4, characterized in that: The solid composite electrolyte further comprises glass fibers, wherein the glass fibers are dispersed in the solid solvent polymer; Optionally, based on the total mass of the solid composite electrolyte, the content of the glass fiber is 0.05 to 10 wt %, preferably 1 to 5 wt %.
6. A method for preparing a solid composite electrolyte, characterized in that: The preparation method comprises the following steps: S1, performing a first mixing treatment on a solid solvent polymer monomer and a lithium supplement agent to obtain a first slurry; S2, performing a second mixing process on the first slurry and the lithium salt to obtain a second slurry; S3, heating and drying the second slurry.
7. The preparation method according to claim 6, characterized in that: The viscosity of the first slurry is 500 to 10000 Cp, preferably 1000 to 3000 Cp; and / or, the solid content of the first slurry is 10-50%, preferably 15-30%; and / or, the viscosity of the second slurry is 50 to 20000 Cp, preferably 50 to 200 Cp; and / or, the solid content of the second slurry is 1 to 20%, preferably 5 to 10%; And / or, the solid solvent polymer monomer is at least one selected from 1,3-epoxypentane, ethylene oxide, vinyl acetate, methyl methacrylate and 1,1-difluoroethylene.
8. The preparation method according to claim 6, characterized in that: In step S1, the conditions of the first mixing treatment include: temperature of 40-60°C, time of 10-120 min, stirring speed of 800-1500 rpm; And / or, in step S2, the conditions of the second mixing treatment include: temperature of 40-60°C, time of 30-60 min, stirring speed of 600-900 rpm; And / or, in step S3, the conditions of the heating treatment include: a temperature of 40 to 60° C. and a time of 30 to 90 min; and / or, the conditions of the drying treatment include: a temperature of 40 to 60° C. and a time of 60 to 150 min.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method further comprises: adding glass fibers in the second mixing process to obtain a second slurry containing glass fibers.
10. A battery, characterized in that: The battery comprises an electrode assembly and an electrolyte, wherein the electrode assembly comprises a positive electrode, a negative electrode and a solid electrolyte layer, and the solid electrolyte layer is a solid composite electrolyte as described in any one of claims 1 to 5 or a solid composite electrolyte prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Composite lithium supplement agent and preparation method and application thereof
CN115425304A
Positive electrode lithium supplementing material, preparation method and application thereof
CN115764013A
Element-doped sulfide solid electrolyte with coating layer and preparation method thereof
CN115995600A
Composite lithium supplement agent suitable for solid electrolyte and application of composite lithium supplement agent in solid-state battery
CN117080442A
Lithium-supplementing solid electrolyte as well as preparation method and application thereof
CN117080539A